Financial Management Behavior in Financial Management Agencies and Regional Assets of Papua Province - Badaruddin, Diah Amanah Putri (Journal of Economics Review (JOER), 2024)
This study explores the factors influencing financial management behavior in the financial management agencies and regional assets of Papua Province. The research delves into the impact of financial attitude, locus of control, and level of education on financial management behavior. The study draws on existing literature to examine the relationship between these factors and financial management behavior. The findings provide insights into the significance of these factors in shaping financial management practices within the context of regional financial autonomy. Understanding these influences is crucial for enhancing financial management policies and practices at the regional level.